(untitled) (REVISTA NODO, 2024)
In the article, a review of the concept of urban sustainability is made since it was coined until the present. The introduction mentions the four variables that make cities unsustainable: extraction and processing of natural materials; energy, materials and water required by the urban metabolism; externalities; and spatial occupation. Methodologically, a time window was established covering from 1987 to 2019, and to avoid biases, the search was conducted in nine languages. The results were: i) the review of 51 articles from 26 countries and five continents; ii) 50 factors that strengthen urban sustainability; iii) two matrices that allow us to assess the frequency and importance of these factors globally and for Latin America and the Caribbean; and iv) a concept of urban sustainability applicable to Latin America and the Caribbean is proposed. It is concluded that there are many factors that must include a public or urban policy that aims to strengthen urban sustainability.